Literacy among Malaysian primary schoolers: how do boys perform relative to girls? - Mohd. Asraf, Ratnawati; Abdullah, Hazlina; Md Zamin, Ainul Azmin (Dumlupinar University, 2016)
The performance of boys in literacy has become an issue of increasing concern around the globe. This paper discusses the results of a study that sought to determine the literacy performance of Malaysian primary schoolers. Using one of the states in the country as a case study, data on approximately 85,000 students from grades 1, 2, and 3 were obtained. Teachers' view were also sought through focus group interviews and journal entries. The results show that although there is an overall improvements in literacy performance in the national language among the students as they go into Grades 2 and 3, girls are found to outperform boys in every screening for all grade levels.